Submerged Culture on the Subject of the Unconscious - Carpes, Maria Cristina (2019)
The purpose of this article is to make points of reflection on hypothesis that culture is submerged in the subject of the unconscious. To this end, we go through a few points of psychic Constitution of the subject, inaugurated by the maternal investment in Freudian lacanianas joints of the proposal with ex-sistance of the subject. The culture takes the place of another, as well as the language and the mother to the infans, in that the subject makes no sexual satisfaction to get to satisfy the desire of Another culture. There's a price to pay as a result of neurosis, the power and destructiveness in life "civilized".